Recent fertility and its proximate determinants in 3 ASEAN countries / Lai Siow Li - Lai, Siow Li (2016)
Cambodia, Indonesia and the Philippines are three out of the four Association of Southeast Asian Nations (ASEAN) countries whose fertility remained above replacement level. Within each country, fertility varies widely across socio-economic sub-groups, resulting mainly from differentials in age at marriage and contraceptive use. Low fertility has resulted in population ageing and labor shortage, giving rise to growing concerns. A better understanding of fertility dynamics is therefore needed to inform policy. This thesis seeks to analyze fertility differentials between Cambodia, Indonesia and the Philippines, and fertility differentials and factors affecting childbearing in each of the three countries. Data for this thesis are taken from the latest Demographic and Health Survey (DHS) in each country under study. DHS covered married women aged 15-49 and collected information on place of residence, couple's education, couple's work status, wealth index, women's household decision-making autonomy, and their attitude towards wife beating by husband. All these were used as predictors of the number of children ever born (CEB). This thesis also studies the association between socio-economic variables and the two main proximate determinants of fertility - age at first marriage and contraceptive use. Bongaarts' model was used to examine the effects of marriage postponement and contraceptive use on fertility. Results from Negative Binomial Regression analysis show that women employed in the non-agricultural sector and wealth index are inversely related to CEB in all three countries after controlling for other variables, women's age and duration of first marriage. Couple's education are negatively correlated with CEB in Cambodia and the Philippines. Disagreeing with wife beating led to fewer children among Indonesian women. The following variables correlate positively with CEB in the multivariate context, which are incongruent with findings from past studies: urbanization in the Philippines, husband's education and employment in Indonesia. Delayed marriage and contraceptive use are the two most important proximate determinants of fertility in all three countries. The effects of socio-economic variables on childbearing are mainly mediated through these two variables, although there are some anomalies across sub-groups in each country. Family planning efforts differ widely across countries, and this has resulted in different level of contraceptive use. Within each country, the differential response to family planning program among socio-economic sub-groups has brought about wide variation in contraceptive use, and hence the fertility differentials. Findings from this thesis show that the fertility behavior in a fast changing world needs to be examined from new perspectives. Emphasis should now be placed on the opportunity costs of childbearing and childrearing, and the lack of childcare support for working women. There is also a need to have more refined composite indicators such as the role of men. One significant finding from this thesis is that the poor in all three countries tend to have more children than those who are better off, which may perpetuate the poverty cycle. Hence, it is necessary to step up the information, education and communication activities and to ensure equal access to contraceptive services to allow couples to plan childbearing accordingly.